The changing nature of work: understanding precarity and the gendered individualisation of risk in post-apartheid South Africa - Mhlana, Siviwe (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2021)
Against the backdrop of workplace restructuring globally, post-Apartheid South Africa is experiencing consistently high levels of unemployment, the deterioration of employment security, and limited improvements in earnings. This trend in the proliferation of low-paid, unstable and otherwise insecure employment has given rise to a segment of the literature that is centred on the growing precariousness of work in a number of different contexts. This thesis reviews empirical work on the changing nature of labour-intensive production in the past two decades, with particular focus on the trends in non-standard, informal and precarious employment. Further, the thesis examines the shift in the gender structure of South Africa's manufacturing sector and how it affects the share in the benefits of employment, particularly with regard to social reproduction. In so doing, the thesis expands the critical theoretical narrative about the challenges of labour under neoliberalism by providing an intersectional perspective of precarious work in post- Apartheid South Africa.
Keywords: Precarious employment; Labor supply -- South Africa; Labor supply -- Statistics -- South Africa; Precarious employment -- South Africa; Informal sector (Economics) -- Employees -- South Africa; Women employees -- South Africa; Women temporary employees -- South Africa